Coxiella burnetii Infection in Livestock, Pets, Wildlife, and Ticks in Latin America and the Caribbean: a Comprehensive Review of the Literature - Epelboin, Loïc; De Souza Ribeiro Mioni, Mateus [UNESP]; Couesnon, Aurelie; Saout, Mona; Guilloton, Edith; Omar, Salma; De Santi, Vincent Pommier; Davoust, Bernard; Marié, Jean Lou; Lavergne, Anne; Donato, Damien; Guterres, Alexandro; et al. (Springer Nature, 2023)
Purpose of the Review: Q fever, a bacterial zoonosis caused by Coxiella burnetii, is reported very heterogeneously in humans in Latin America. The objective of this study was to review the data on Coxiella burnetii Infection in animals in Latin America and the Caribbean. Recent Findings: A comprehensive literature review was carried out in the 47 countries and territories of Latin America on various search engines and grouped into four groups: livestock, pets, wildlife, and ticks. Summary: Thus, 113 studies were selected between 1950 and 2022. Among the 47 countries, only 25 (53%) had at least one publication related to C. burnetii infection in animals. The most productive country was Brazil (N = 51), followed by French Guiana (N = 21), and Colombia (N = 16). Studies in livestock from 20 countries have shown widely varying country-to-country rates of seroprevalence, ranging from 0 to 67%. Some studies from seven countries, especially French Guiana and Brazil, found antibodies and sometimes positive PCR in dogs and cats, generally in the context of investigations around human clustered cases. Knowledge remained fragmented about infection in wildlife from only five countries (Chile, Colombia, Brazil, French Guiana, and Uruguay). C. burnetii infection was identified by PCR in Chiroptera (7 species), Rodentia (6 species), Suina (2 species), Xenartha (1 species), Cingulata (1 species), and Perissodactyla (1 species). Studies on Coxiella sp. in ticks have been performed in 11 countries, mostly in Brazil, and mainly found Coxiella-like endosymbionts. Thus, data on C. burnetii infection in animals are sparse and incomplete in Latin America and the Caribbean, and more research is warranted.
Keywords: Animal health; Caribbean; Cattle; Coxiella burnetii; Latin America; Ticks; Wildlife; Zoonosis